Evaluation Of The Application Of Additional Punishment For Chemical Castration In Handling Perpetrators Of Sexual Violence Against Children Is Reviewed From Government Regulation (Pp) Number 70 Of 2020 Concerning Procedures For The Implementation Of Chemical Castration - Yoldy Israq; Suci Ramadani; Muhammad Arif Sahlepi (Utan Kayu Publishing, 2026)
This study aims to evaluate the application of additional punishment in the form of chemical castration to perpetrators of sexual violence against children as stipulated in Government Regulation (PP) Number 70 of 2020 concerning Procedures for the Implementation of Chemical Caster. The birth of the PP is the government's effort to provide maximum protection for children as victims of sexual crimes, as well as a form of deterrent effect for perpetrators. The research method used is normative juridical research with a statutory approach and a conceptual approach. Data was obtained through literature studies by examining laws and regulations, legal doctrines, and related literature. The results of the study show that the application of chemical castration punishment still faces a number of challenges, both from the judicial, medical, and human rights aspects. From a juridical perspective, Government Regulation No. 70 of 2020 has provided technical guidelines related to the implementation mechanism, but there are still gaps in synchronization with other regulations, including the Criminal Code and health-related laws. From a medical perspective, chemical castration procedures require professional medical personnel and adequate health facilities, while from a human rights perspective, there is a debate about the relevance of this punishment to the principle of respect for human dignity. Thus, an evaluation of the application of chemical castration needs to be carried out comprehensively in order to ensure the protection of children's rights without ignoring the principles of justice and humanity.